Механика движения двухфазного потока в диффузоре оросителя с предварительным газонасыщением - Kachanov Игорь; Karpenchuk Игорь; Pavlyukov Сергей (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2012)
Coverning equations of the motion of two-phase flow, which allows to calculate the distribution of the mean pressure in the diffuser length, as well as to determine the pressure loss in the diffuser, which makes it possible to design the output section of the hydraulic system of hydrodynamic resistance, offers an injector in a given mode.